The Effect of Using KWL Technique on EFL Student' Reading Ability at SMAN 2 Gunung Talang - Ranover, Ranover; Fatimah, Sitti (Journal of English Language Teaching, 2024)
This research seeks to determine the effect of using KWL technique on EFL students’ reading ability at SMAN 2 GUNUNG TALANG. For this study pre-experimental with one group pretest posttest design was used. The sample in this study is class XII IPA 1 with 33 students. The data were collected from pretest and posttest which were given to the students. The results indicated that there was an improvement in a scores between the pretest and the posttest showed that there is improvement between pretest and posttest score. The pre-test score mean is 45.48 with 6 students received very poor classification, 18 students received poor classification, and 9 students received fairly classification. The post-test score mean is 50.24 with there is no student received very poor classification, 24 students received poor classification, 8 students received fairly classification, and 1 student received fairly good classification. It means that student’ posttest score were higher than pretest score, demonstrating that the KWL technique was effective in teaching reading